Warppls Analysis Application For Effects Of Personality And Commitment On The Engagement Of Ngrebeg Mekotek Traditional Actors In Munggu Village, Bali - Solimun (International Journal of Advanced Science and Technology, 2020)
In the globalization era, it is undeniable that more and more people are forgetting the traditions of their native regions. Ngrebeg Mekotek is one of the traditions that continue to this day. This study focuses on knowing the relationship between personality, commitment, and engagement of the perpetrators of the Ngrebeg Mekotek tradition. WarpPLS is a development of PLS analysis that can be used to determine the influence of relationships between variables. This study uses primary data obtained from distributing questionnaires to the perpetrators of the Ngrebeg Mekotek tradition using judgement sampling techniques.  The results of the analysis using WarpPLS found a positive relationship between personality with commitment, commitment to the engagement of the perpretators of the Ngrebeg Mekotek tradition, and personality to the engagement of the perpretators of the Ngrebeg Mekotek tradition. Based on this relationship, it can be seen that personality variable have a greater contribution than the commitment variable towards the engagement of the perpretators of the Ngrebeg Mekotek tradition.